(untitled) (Eurasian Journal of Ecology, 2021)
Currently, one of the most pressing problems in animal husbandry is the lack of feed protein in the production of feed. One of the main directions of the modern food industry is the production of protein feed and feed additives for animal husbandry. Due to the lack of feed for animals and birds in animal husbandry, special attention is paid to microbial biomass as a source of protein. Microbial biomass production is considered the only way to eliminate protein deficiencies in animal diets. Enrichment of agricultural waste with microbial protein makes it possible to expand stocks of raw materials for the production of feed, as well as to solve environmental problems arising from the introduction of processing technologies. The aim of the study is to isolate highly active yeast cultures from various natural substrates and collection crops in order to obtain an effective fodder protein for animal husbandry. In the work, 6 yeast strains were used, including 3 yeast strains Rhodotorula glutinis var glutinis R12, Torulopsis kefyr var.kumis T-17, Candida inconspicua TD-6 from the laboratory of applied microbiology of KazNU named after Al-Farabi. Three yeast strains were isolated from dairy products and plant substrates. These strains hold promise for providing complete feed protein for farm animals. Key words: milk whey, microbial diversity, fodder protein, yeast, natural substrates.